Protective roles of cytoplasmic p21Cip1/Waf1 in senolysis and ferroptosis of lung cancer cells. Issue 12 (30th August 2022) - Koyanagi, Akira; Kotani, Hitoshi; Iida, Yuichi; Tanino, Ryosuke; Kartika, Irna D.; Kishimoto, Koji; Harada, Mamoru
Abstract: Objective: Therapy‐induced senescent cancer cells increase the expression of the cyclin‐dependent kinase inhibitors p16 Ink4a and p21 Cip1/Waf1 . Given that p21 regulates not only the cell cycle but also cell death, we investigated the roles of p21 in cell death using a p16‐negative A549 human lung adenocarcinoma cell line. Methods: Senescence was induced by doxorubicin (DXR) or pemetrexed (PEM). The protein expression of p21 was examined by immunoblot. Cell death, reactive oxygen species (ROS) and lipid peroxidation were determined by flow cytometry. ABT‐263 and ABT‐737 were used as senolytic drugs. In vivo growth of A549 cells with different levels of p21 and their sensitivity to PEM were examined in xenograft models. Results: DXR‐induced senescent A549 cells increased the expression of cytoplasmic p21, and the sensitivity to ABT‐263 was augmented in p21‐knockout A549 (A549‐KOp21) cells. A similar senolytic effect was observed when PEM was combined with ABT‐737. PEM alone induced a higher level of non‐apoptotic cell death, ferroptosis, in A549‐KOp21 cells than in A549 cells. Although there was no difference in the level of lipid peroxidation, ROS levels were higher in PEM‐treated A549‐KOp21 cells than in PEM‐treated A549 cells. A loss of p21 increased the sensitivity of A549 cells to PEM both in vitro and in vivo. A clinical database analysis showed that CDKN1A high lung adenocarcinoma patients had a poorer prognosis compared to CDKN1A low patients. Conclusion: Cytoplasmic p21, which was increased in therapy‐induced senescent lung cancer cells, plays protective roles in senolysis and ferroptosis. Abstract : Doxorubicin or pemetrexed could induce senescence in p21‐expressing parental A549 cells and increase the expression of cytoplasmic p21. However, such drug‐induced senescent A549 cells were relatively resistant to apoptosis by senolytic drugs. By contrast, p21‐knockout A549 (A549‐KOp21) cells increased their sensitivity to senolytic drugs. On the other hand, pemetrexed induced a higher level of non‐apoptotic cell death, ferroptosis, in A549‐KOp21 cells than in A549 cells. These findings highlight the protective roles of cytoplasmic p21 against senolysis and ferroptosis in therapy‐induced senescent lung cancer cells.